KeefektifanPembelajaranKooperatif Tipe CIRC Berbantuan Alat PeragaterhadapKemampuanPemecahan Masalah MateriSegiempat - Fitri, Amalia (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The research was aimed at first investigating the problem solving ofstudents who were taught with the CIRC method especially within thematerial of quadrilateral, and second investigating wether the studentscould reach the competence expected. The results of the researchshowed that the students taught with CIRC model were better inachieving in competence. In conclusion this model of teaching could beused to improve student’s problem solving skills both for the material ofquadrilateral and for other materials having similiar characteristics.Key Word : CIRC type of cooperative learning model, problem solvingskill.